Mengenal Flipped Classroom sebagai Salah Satu Solusi dalam Blended Learning - Retno Nengsih; Nurul Hikmah; Mailizar Mailizar (Universitas Pahlawan Tuanku Tambusai, 2023)
PKM activities are carried out to improve the literacy of SMK Bhakti Idhata teachers' learning strategies, especially when blended learning is used.As is well known, the COVID-19 pandemic has changed the face of education in Indonesia in a relatively short time. The learning system, was originally carried out face-to-face, changed to online and then to a combination of online and offline. It is called blended learning. The extreme change made the teachers confused in choosing which methods and strategies should be applied. This PKM activity was carried out in 3 stages, namely the initial stage in the form of a survey and preparation, the core stage in the form of activity implementation, and the final stage in the form of evaluation. The training is delivered online and focuses on introducing the flipped classroom as a blended learning strategy solution. As a result, this activity provides teachers with new experiences in using learning models in blended learning.